Small and Medium Scale Enterprises (SMES) Financing and Sustainable Economic Growth in Nigeria: Array - Olowookere , Johnson Kolawole; Hassan , Christiana Onyohu; Adewole , Aliu Olusola; Aderemi, Timothy Ayomitunde (The Journal of Accounting and Management, 2021)
The investigation into the relationship between SMEs financing and sustainable economic growth between 1992 and 2019 has been carried out in this study. After various pre-estimation tests such as unit root and cointegration were carried out, the study utilized Fully Modified Ordinary Least Square and Granger causality approach. Consequently, the following important findings were emerged from this study as follows; broad money supply and GDP growth rate have insignificant inverse relationship. Commercial banks loans to SMEs and GDP growth rate possess a positive and significant relationship. Gross fixed capital formation and commercial bank total credit to private sector showed an insignificant positive relationship with GDP growth rate. Moreover, a unidirectional causality flows from broad money supply to gross fixed capital formation. Similarly, one way feedback runs from GDP growth rate to commercial banks loans to SMEs. Hence, it could be submitted that SMEs financing contributed to sustainable economic growth in Nigeria in one hand. And sustainable economic growth is the motivation behind the commercial banks loans to SMEs in Nigeria on the other hand. From these important findings that emerged from this study, it is important to state that any time the goal of policymakers in Nigeria is sustainable economic growth, SMEs financing should be their priority. And as such, the Central Bank of Nigeria should embark on policy measure that will ensure the priority of the commercial banks’ credit policy in the direction of SMEs on a sustainable manner.